THE EFFECT OF TEACHING ABILITY AND DISCIPLINE OF LECTURERS ON STUDENT SATISFACTION FACULTY OF ISLAM, MUHAMMADIYAH UNIVERSITY OF BANJARMASIN: THE EFFECT OF TEACHING ABILITY AND DISCIPLINE OF LECTURERS ON STUDENT SATISFACTION FACULTY OF ISLAM, MUHAMMADIYAH UNIVERSITY OF BANJARMASIN - Safitri, Dewi; taufik, herman; putri, noorhalimah (Tawazuna, 2022)
The objectivites of this study include: 1) Knowing and analyzing the performance of lecturers on the teaching abilities of students of the faculty of islamic religion, university of muhammadiyah banjarmasin. 2) Knowing and analyzing the discipline of lecturers on the teaching and learning process of students of the faculty of islamic religion UM Banjarmasin. 3) Knowing and analyzing student satisfaction on the teaching performance of lecturers at. This type of research is quantitative research because this research emphasizes the influence on the processed numerical data. The population of 50 students became 45 students using the Simple Random Sampling technique